Kinetic study on vinegar production using star fruit juice - Abdul Karim, Mohamed Ismail; Kamaruddin, Noor Izzaida (IIUM Press, 2011)
A study was undertaken to produce Star fruit vinegar (Averrhoa carambola) juice through double stage fermentation with the use of microorganisms namely Saccharomyces cerevlszae and Acetobacrer acetl. The star fruit juice with optimum glucose concentratIOn (20%) was used and growth kinetic study of the cultures to optimize operational conditions ( agitation speed and inoculums size) in 2L bioreactor for production of star fruit vinegar was conducted .An experimental design using the Central Composite Design by Design Expert software, where the main factors Impeller speed(rpm) and moculums sizes (% inoculums) were optimized affecting the production of acetic acid in fruit Juice during fermentation. Sampling of the were done every 12 hours during 4 days of fermentation time to analyze cell concentration (OD 600 nm), Total Cell Number, cell dry weight, reducing sugar, ethanol and acetic acid production. On the different combination of factors for all 9 runs of experiment conducted, It was found optimum production of acetic acid was achieved with agitation speed of 250 rpm and 5% inoculums sizes where highest ethanol production of 17.8% or 150.34 g/L. and 2.76% acetic acid (TA) was obtained. This combination of parameters produces the highest specific growth rate, u and highest yield which are 0.859 and 0.342 g/g of the culture was obtained.